Development Of High Reflectance Glaze - Sobberi, Wan Nuraimi Athirah Wan (Universiti Sains Malaysia, 2017)
Ceramic tiles with cooling function were believed to be one of sustainable solution for reducing building electrical energy consumption for cooling. Many pigments have been studied as cooling materials and among them, titanium dioxide (TiO2) showed promising properties. Therefore, TiO2 was selected in this study to develop high reflectance glaze for cooling tile application. Different particle size of TiO2 (0.9μm, 1.2μm and 1.4μm) were added in different types of commercial glazes; white and vetrosa supplied by Guocera Sdn. Bhd. Glazing were perform using dipping method for 5 seconds. Then, the dried glaze tile using white glaze was fired at temperature 1130°C for 15 minutes while dried glaze tile using vetrosa glaze was fired at temperature 850°C for 15 minutes. Samples were then characterized using X-Ray Diffraction (XRD), Scanning Electron Microscope (SEM), the coefficient of thermal expansion (CTE), physical observation and UV-Vis analysis. SEM analysis show the distribution of finer particle size of TiO2 dispersed more uniformly lead to smoother glaze surfaces compared to bigger particle size added. Thus, increase the opaque appearance of the glazes. As the opacity of glaze increase, the reflection is also increase. UV-Vis analysis show with addition of TiO2 can increase the reflectance of samples. TiO2 with smaller particle size (0.91 ) in white glaze gave high reflectance which is 91% with good opaque appearance. This proves that by altering the properties of TiO2 powder will improve its reflectance properties.